Epilepsy: A Review - Kabir, Md Shahriar; Rahman, Syed Wahidur; Ahmad, Quamruddin (TAJ: Journal of Teachers Association, 2011)
Epilepsy is a neurological problem which is a cause of sufferings for the common people because of lack of proper scientific knowledge. The incidence of epilepsy is about 0.3 to 0.5% while the prevalence is about 5 to 10 people per 1000. Newer concepts about aetiopathogenesis, classification and treatment modalities are described in brief in this review article. DOI: http://dx.doi.org/10.3329/taj.v14i2.8398 TAJ 2001; 14(2): 99-103